Synthesis, Characterization, and Antimicrobial Evaluation of new Ibuprofen Derivatives - Mohammed Muhsin Jabber, mohammed k. Hadi (Pakistan Journal of Medical & Health Sciences, 2022)
A new series of ibuprofen derivatives were synthesized and tested against the microbial activity. P_amino ethyl benzoate (compound I) was prepared, then coupled with ibuprofen acyl chloride (compound II) to give ethyl 4-(2-(4-isobutylphenyl) propanamido) benzoate (compounds III). Hydrazine hydrate 99% was added to compound III to synthesized N-(4-(hydrazinecarbonyl) phenyl)-2-(4-isobutylphenyl) propenamide (compound IV). Finally compound IV coupled with different aldehydes (1. Benzaldehyde (Va) 2. Salicylaldehyde (Vb) 3. 4_hydroxybenzaldehyde (Vc) 4. Vanillin (Vd) respectively to form target compounds. Identifications and characterization of these compounds were done by using Fourier Transform Infrared Spectroscopy (FTIR), and 1 HNMR analyses. The antimicrobial results showed that compounds (Va has low activity, Vd has high active, Vb and Vd has the moderate activity) against gram positive bacteria (Staphylococcus aureus and Streptococcus pyogenes) and gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa) at concentration 500 µg/mL. Vd was the only compound that has antifungal activity against Candida ablicans compared to fluconazole.